2013
DOI: 10.3329/cbmj.v2i1.14177
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Timing of Admission in Labour on Subsequent Outcome

Abstract: To examine the effect of timing at which women admitted either in active or latent phase of spontaneous labour on subsequent outcome. This cross-sectional study was conducted at labour ward, department of Obstetrics and Gynaecology, BSMMU hospital, Dhaka, Bangladesh, from August 2007 to November 2007, where data were collected prospectively. A total of 60 women with term, singletone pregnancy, cephalic presentation with spontaneous onset of labour admitted in labour either in active or latent phase were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…This is similar to a study done in USA [7]. Regarding mode of delivery, studies in Bangladesh and Ethiopia found that normal vaginal delivery was significantly higher in active phase of labor than in latent phase of labor (p < 0.05), the finding which relate to this study (p < 0.006) [8,11]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is similar to a study done in USA [7]. Regarding mode of delivery, studies in Bangladesh and Ethiopia found that normal vaginal delivery was significantly higher in active phase of labor than in latent phase of labor (p < 0.05), the finding which relate to this study (p < 0.006) [8,11]. …”
Section: Discussionsupporting
confidence: 91%
“…Perineal injury was found in 2(5.7%) and cervical tear was found in 1(2.9%) in latent phase of labor whereas no injury was found in active phase of labor in the study in Bangladesh [8]. PPH in the active phase group in this study occurred largely among primiparous women in approximately 50% of cases; thus the difference in labour complication pattern from other studies could be attributed to human resource constraints.…”
Section: Discussionmentioning
confidence: 62%
“…However our results were not consistent with the studies done by Albassam AN (58.3% vs 41.5% p < 0.05) [11] and Jessica Burns SN (80.4% vs 48.9%, p < 0.05) [12] . Regarding mode of delivery, our study found that normal vaginal delivery was statistically significantly higher in active phase of labor than in latent phase of labor which was similar to the study done by Janna et al [13] Caesarean section was more Section: Obstetrics & Gynaecology in latent phase compared to active phase of labor group in this study which is similar to study by Bailit J et al [8] . Leitch and Waker [14] demonstrated failure to progress remain the major indication underlying the decision to perform caesarean section followed by fetal indication.…”
Section: Discussionsupporting
confidence: 82%
“…Here major indication of caesarean section was dystocia which included failure to progress followed by fetal distress. On assessment of maternal complications, our study showed that more women had perineal tear (6.2%) and PPH (6.2%) in group 1, similar to this, Bailit JL et al [8] observed more cases of PPH (5.7%) in latent phase group and none was found in active phase group whereas Janna JR [13] observed no differences in PPH in the two groups. As compared to other studies, there was no difference between the birth weights but difference in outcome regarding asphyxia might have influenced by the strict exclusion criteria of the present study, which enrolled only low risk term pregnancy.…”
Section: Discussionsupporting
confidence: 72%
“…Evidence from large international retrospective cohort studies [1][2][3][4][5][6] suggests between 10.2% [1] and 58.5% [2] of women are admitted to hospital in latent phase ('early') labour. International guidelines recommend a delay in hospital admission during the early phase of labour by supporting women to stay at home [7,8].…”
Section: Introductionmentioning
confidence: 99%